2016
DOI: 10.1063/1.4960401
|View full text |Cite
|
Sign up to set email alerts
|

A simple photoionization scheme for characterizing electron and ion spectrometers

Abstract: We present a simple diode laser-based photoionization scheme for generating electrons and ions with well-defined spatial and energetic (≲2 eV) structures. This scheme can easily be implemented in ion or electron imaging spectrometers for the purpose of off-line characterization and calibration. The low laser power ∼1 mW needed from a passively stabilized diode laser and the low flux of potassium atoms in an effusive beam make our scheme a versatile source of ions and electrons for applications in research and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Over this short measurement time, the data quality is not affected by long-term drifts of the laser system. Finally, the 3D PMD is energy-calibrated using the procedure described in [93]. Throughout the paper, we show energy-calibrated PMDs.…”
Section: Methodsmentioning
confidence: 99%
“…Over this short measurement time, the data quality is not affected by long-term drifts of the laser system. Finally, the 3D PMD is energy-calibrated using the procedure described in [93]. Throughout the paper, we show energy-calibrated PMDs.…”
Section: Methodsmentioning
confidence: 99%
“…The patterns that arise appear as expanded horizontal stripes with a suppressed velocity spread. Exploiting the resulting spatial information facilitated the spatially resolved mass spectrometric (MS) imaging of analytes on surfaces and molecular dynamics studies. , In particular, the latter showed the spatial height and width of formed atomic and molecular ions and the overall SMI of the AB/MB profiles. ,, In addition, molecular ion visualization helped the temporal and spatial overlap of two laser beams in a noncollinear arrangement, characterizing the 1D, 2D, and 3D imaging modes, and mapping the initial source distribution of electron emission from a surface . Moreover, we demonstrated that SMI assists in aligning and overlapping multiple laser beams for monitoring ionization-loss stimulated Raman spectra and in pump–probe experiments in general.…”
Section: Introductionmentioning
confidence: 90%
“…A lens with 175 mm focal length was mounted on a translation stage to focus the light into the center of the interaction region. By shifting the focus position in the interaction region horizontally and vertically, we calibrated the positions on the detector and the ion time-offlight, respectively 50 . Furthermore, a gratingstabilized diode laser is at our disposal to implement a simple scheme for photoionization of potassium atoms for precise calibration measurements 50 .…”
Section: Spectrometer and Vmi Potentialsmentioning
confidence: 99%